1980
DOI: 10.1126/science.7367859
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Expression of Wilson's Disease in Cell Culture: A Diagnostic Marker

Abstract: Wilson's disease fibroblasts have an elevated intracellular copper concentration as compared to cultured control cells. A decreased ratio of copper to protein was observed in cytoplasmic protein (or proteins) having a molecular weight greater than or equal to 30,000 in Wilson's disease cells. The results of this culture study indicate its potential importance in the early unequivocal diagnosis of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Although recent studies (18,19) have reported increased copper levels in cultured fibroblasts of patients with WD, the observation has not been sufficiently established (1), and the applicability of this method for prenatal diagnosis of WD has not yet been tried (20). It is interesting to note that the gene for the copper-containing protein ceruloplasmin appears to be located on chromosome 3 (21,22).…”
mentioning
confidence: 99%
“…Although recent studies (18,19) have reported increased copper levels in cultured fibroblasts of patients with WD, the observation has not been sufficiently established (1), and the applicability of this method for prenatal diagnosis of WD has not yet been tried (20). It is interesting to note that the gene for the copper-containing protein ceruloplasmin appears to be located on chromosome 3 (21,22).…”
mentioning
confidence: 99%
“…(1980). For Wilson's disease (McKusick 27790), Chan et al (1980) found elevated intrace!lular copper concentrations but Camarakis et al (1980) found them to fall within the normaI range, as is the case here. However, copper content is not constant for the same fibroblasts after several passages.…”
mentioning
confidence: 49%
“…Unless a biochemical marker or other mutant gene product is recognized at or near birth, the congenital nature of the disorder is unproven. Examples of this include Huntington's Disease (2), Wilson's Disease (4), and Marfan's Syndrome (17). When a marker is identifiable, as in phenylketonuria (20), the disease is recognized as congenital.…”
Section: Discussionmentioning
confidence: 99%